ANALISIS KEMAMPUAN MEMBACA SISWA KELAS 1 SDN 009 KEPAU JAYA KECAMATAN SIAK HULU KABUPATEN KAMPAR - Halim, Muhammad; Hermita, Neni; Kurniawan, Otang (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2020)
The background of this research is the problem of reading ability of first gradestudents in SDN 009 Kepau Jaya, Siak Hulu Subdistrict, Kampar Regency. The students have difficulty recognizing letters, even though the teacher often repeats the letters in front of the class, saying words, and matching pictures with writing when the teacher uses the task of matching images with children's writing, and it tends to be less able to do it. This study aims to analyze the first grade students’ reading ability . The population and sample in this study were all first grade students, 30 students, from SDN 009 Kapau Jaya, Siak Hulu Subdistrict, . The method used in this research is quantitative. The data collection technique used was observation and they were analyzed to find out the results of descriptive statistics that illustrated the level of first grade students’ reading ability. Based on the results of the study it was found that the first grade students’ reading ability was low. This can be seen in the category of scores obtained by students where 60% of students are in the low initial reading ability, while the remaining 40% of students are in moderate reading ability. This is influenced by physiological factors, intellectual factors, environmental factors, and psychological factors.